Communication, digital media and future: new scenarios and future changes - Gola, Elisabetta; Volterrani, Andrea; Meloni, Fabrizio (UNICApress, 2022)
Digital media, technology, new theoretical perspectives have revolutionized the ways of interacting among individuals, acquiring information and knowledge, teaching, behaving in multicultural society and so on and so forth. The impact of new ways of communicating, social media, political platforms on daily lives is evident. Multifaced and different aspects of these topics have been discussed in the VI World conference on Media and Communication (MEDCOM), which was supposed to be held in Cagliari, in May 2020, and it has been postponed to June 2021, online. During that year, communicating revealed even more relevant for citizen live. We assisted to the great importance of best practices in crisis communication, and the critical situations generated by fake news and information overload.